THE EFFECT OF FOREIGN INVESTMENT ON THE IRAQI NATIONAL INCOME - Waleed A. Hassen (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The study aims to find In the long run stable relation between Gross domestic product represented by economic the growth and direct foreign investment in the long and short terms, so the study included data series in the time period (1990-2020), and co-integration test Granger causality and error correction vector was used to know the direction of the relation between the study variables and the relation nature of balance in the term long or short, and It is obtained that there is a relation is a one-way causation, As transmission is done long-term from foreign direct investment to economic growth. The possible explanation is due to the drop in oil prices, as Iraq depends directly and mainly on oil exports in its economy, as well as because of the rampant administrative corruption in the country, that is extended its effects to all sectors.